Comparison of Different Biomass Pretreatment Techniques and Their Impact on Chemistry and Structure - Singh, Seema; Cheng, Gang; Sathitsuksanoh, Noppadon; Wu, Dong; Varanasi, Patanjali; George, Anthe; Balan, Venkatesh; Gao, Xiadi; Kumar, Rajeev; Dale, Bruce E.; Wyman, Charles E.; Simmons, Blake A. (Frontiers in Energy Research, 2015)
Pretreatment of lignocellulosic biomass is a prerequisite to overcome recalcitrance and allow enzyme accessibility to cellulose and maximize product recovery for improved economics of second-generation lignocellulosic bio-refineries. Recently, the three US-DOE funded Bioenergy Research Centers (Joint Bioenergy Institute (JBEI), Great Lakes Bioenergy Research Center (GLBRC), and BioEnergy Science Center (BESC)) compared ionic liquid (IL), dilute sulfuric acid (DA), and ammonia fiber expansion (AFEXTM) pretreatments and published comparative data on mass balance, total sugar yields, substrate accessibility, and microbial fermentation (Biotechnology for Biofuels 7: 71; 72 (2014)). In this study, corn stover solids from IL, DA, and AFEX pretreatments were compared to gain comprehensive, in-depth understanding of induced morphological and chemical changes incorporated to corn stover, and how they overcome the biomass recalcitrance. These studies reveal that biomass recalcitrance is overcome by combination of structural and chemical changes to carbohydrates and lignin after pretreatment. Thermal analysis indicates that AFEX and IL pretreated corn stover showed a lower thermal stability while DA pretreated corn stover showed the opposite. The surface roughness variations measured by SANS were correlated to the removal and redistribution of biomass components and was consistent with compositional analysis, AFM and confocal fluorescence imaging results. With AFM and confocal fluorescent microscopy, lignin was found to be re-deposited on cellulose surface with average cellulose fiber width significantly decreased for DA pretreated corn stover (one third of IL and AFEX). HSQC NMR spectra revealed a ~17.9% reduction of β-aryl ether units after AFEX, ~59.8% reduction after DA and >98% reduction after IL. Both NMR and SEC showed similar patterns of lignin depolymerization with highest degree of depolymerization observed for IL followed with DA and AFEX.